Psychosomatic research in ischemic cardiopathy. - Cardoso, G (1992)
The need felt in the last decades for research concerning the psychosocial aspects of Ischaemic Heart Disease is emphasized. Different methodologies of research in this area are described, as well as their usefulness in different kinds of studies. The main areas of research in Ischaemic Heart Disease and the more recent advances in some of them are mentioned. Finally, the most promising fields for future research in Ischaemic Heart Disease are emphasized.